(untitled) (American Journal of Islam and Society, 2002)
This is a well-researched and carefully thought out book on the highly complex issue of the Qur’ an ’s self-referential terms to its own status as Scripture. Particularly illuminating are the author, Daniel Madigan’s, clear and profound engagements with the semantic content of key Qur’anic words like kitab, mushaf, qur’an, dhikr, tanzil. and wahy, and his discussion of the inter-relatedness of these tenns. Madigan successfully problematizes particularly the key terms kitab and Qur’an since, as he shows, their meanings can be fairly fluid and their essence cannot be easily and crudely reduced to a rigid demarcation between orality and "writtenness" alone. A central focus of his book is indeed the tension between the orality and the written nature of Islam’s sacred scripture, already suggested in the name given to it, al-Qur’an, which itself may be translated as ’’the Recitation," and "the Reading." Madigan stresses the primacy of the oral nature of the Qur’an; in his (rather brief) discussion of the terms kalam Allah (the speech of God) and kitabAl/ah (the book of God), he states, ... the focus on the ontological status of the Qur’an [as represented in the usage of the term kalam Allah] may be not merely the result of speculation but rather an attempt to recover something that was lost when the concepts of kitab Allah and Qur’an were collapsed into the content of the mushaf. Chapters 2 - 4 provide a fine and nuanced exposition of the Qur’anic conception of kitab, which, as Madigan persuasively suggests, has to do with divine, timeless authority becoming manifest in the human, timebound world. The difference between Qur’an and kitab is therefore, not merely a question of display or storage, through the medium of the human voice in the fonner and through written composition in the latter, but has to do rather with the Qur’an’s origin, that is, "its author and the source of its composition." ...